NILAI MPN (Most Probable Number) DAN DETEKSI BAKTERI Esherichia PADA MINUMAN ES JERUK PERAS di KOTA PONTIANAK - Ratna, Ratna; Rahmawati, Rahmawati; Mukarlina, Mukarlina (Universitas Tanjungpura, 2019)
Iced squeezed orange drinks is one one of processed drinks that made from orange. Good drinking water should not contain pathogenic bacteria or organisms that may harm human health. Coliform is one ofbacteria that may cause disease in humans and being used as indicator bacteria of pathogenic bacteria. This research was aimed to know the MPN value number of coliform bacteria and to identify the bacterial presence of genus Escherichia in iced squeezed orange drinks sold in Pontianak City. The sampling used random sampling method. MPN method was used in order to know the number of coliform in iced squeezed orange drinks in Pontianak City. MPN test result obtained the lowest index value of MPN/mL was 0,14/mL in sample in subdistrict Pontianak City and the highest index value in four subdistricts in Pontianak City was MPN/mL >24,00/mL. It was showed that five samples exceed normal limits in accordance with SNI standards SNI 01-3839-1995 based on Permenkes No 492/MENKES/per/IV/2010. Identification resultshowed the bacterial genus of coliform obtained was member of genus Escherichia.